Microcalorimetric study of Escherichia coli aerobic growth: kinetics and experimental enthalpy associated with growth on succinic acid. - Dermoun, Z (1979)
A new batch calorimeter was used to study the aerobic growth of Escherichia coli in a minimal containing a growth-limiting concentration of succinic acid. The shape of the thermograms obtained was simple when the energy source was the only growth-limiting factor and showed a stationary phase when the oxygen transfer was limiting. The experimentally determined value of the heat production during growth was found to be significantly lower than the heat of combustion of the succinic acid corrected for the assimilated-substrate fraction. An interpretation has been given to explain the difference between the experimental and the theoretical values.